New β-Propellers Are Continuously Amplified From Single Blades in all Major Lineages of the β-Propeller Superfamily - Pereira, Joana; Lupas, Andrei N. (Frontiers in Molecular Biosciences, 2022)
β-Propellers are toroidal folds, in which consecutive supersecondary structure units of four anti-parallel β-strands – called blades – are arranged radially around a central axis. Uniquely among toroidal folds, blades span the full range of sequence symmetry, from near identity to complete divergence, indicating an ongoing process of amplification and differentiation. We have proposed that the major lineages of β-propellers arose through this mechanism and that therefore their last common ancestor was a single blade, not a fully formed β-propeller. Here we show that this process of amplification and differentiation is also widespread within individual lineages, yielding β-propellers with blades of more than 60% pairwise sequence identity in most major β-propeller families. In some cases, the blades are nearly identical, indicating a very recent amplification event, but even in cases where such recently amplified β-propellers have more than 80% overall sequence identity to each other, comparison of their DNA sequence shows that the amplification occurred independently.